2018
DOI: 10.1111/odi.12822
|View full text |Cite
|
Sign up to set email alerts
|

Chk2 deficiency alleviates irradiation‐induced taste dysfunction by inhibiting p53‐dependent apoptosis

Abstract: Chk2 deficiency downregulated the expression of p53 and inhibited cellular apoptosis, partly contributing to the radioprotective effect on taste cells, but did not alter oxidative stress levels, antioxidant ability, and oxidative DNA damage in taste buds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Radiation xerostomia is caused by a series of histological changes in salivary glands following radiation, including cell death, cell atrophy, focal infiltration, and mild fibrosis 16 . The main cause of dysgeusia induced by radiotherapy 17 is the damage of basic and differentiated taste cells in taste buds. The primary cause of radioactive oral mucositis 18 is the direct damage to the oral epithelium from radiation therapy, including activation of various inflammatory pathways, resulting in the upregulation of inflammatory cytokines and other tissue damage molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation xerostomia is caused by a series of histological changes in salivary glands following radiation, including cell death, cell atrophy, focal infiltration, and mild fibrosis 16 . The main cause of dysgeusia induced by radiotherapy 17 is the damage of basic and differentiated taste cells in taste buds. The primary cause of radioactive oral mucositis 18 is the direct damage to the oral epithelium from radiation therapy, including activation of various inflammatory pathways, resulting in the upregulation of inflammatory cytokines and other tissue damage molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on reducing dysgeusia, Qiang Guo et al [69] reported that sirtuin-1 inhibitors in taste bud organoids promoted taste stem cell survival after irradiation. Similarly, Yuan et al [70] reported that irradiation-induced dysgeusia was reduced by inhibiting apoptosis via p53 in gustatory cells in checkpoint kinase 2 knockout mice.…”
Section: Radiation-induced Taste and Smell Impairmentmentioning
confidence: 92%
“…[7] miR-122-5p overexpression or CCAR1 silencing, combined with IR, significantly reduces the levels of p-CHK2 and enhances radiosensitivity, indicating that CHK2 is an important regulatory kinase in the DNA damage response. [40,65] Zhang et al [66] reported that miR-31 suppresses NF-kB signaling pathways by targeting serine/threonine kinase 40, thereby improving RC radiotherapy sensitivity. Moreover, it is possible to improve sensitivity to radiation by promoting DNA damage after radiotherapy.…”
Section: Mirnas Affect the Response To Rc Radiotherapy By Regulating ...mentioning
confidence: 99%
“…In a study of the relationship between miR-100 and radiotherapy for RC, miR-100 was found to be involved in radiation-induced apoptosis and to modulate the sensitization of CCL-244 cells to radiation by enhancing radiation-induced DNA damage repair [7] . miR-122-5p overexpression or CCAR1 silencing, combined with IR, significantly reduces the levels of p-CHK2 and enhances radiosensitivity, indicating that CHK2 is an important regulatory kinase in the DNA damage response [40,65] . Zhang et al [66] reported that miR-31 suppresses NF-κB signaling pathways by targeting serine/threonine kinase 40, thereby improving RC radiotherapy sensitivity.…”
Section: Relationship Between Mirnas Dna Damage Repair and Radiothera...mentioning
confidence: 99%